2022
DOI: 10.3390/ijerph19137588
|View full text |Cite
|
Sign up to set email alerts
|

Skin Toxicity of Selected Hair Cosmetic Ingredients: A Review Focusing on Hairdressers

Abstract: The safety assessment of cosmetics considers the exposure of a ‘common consumer’, not the occupational exposure of hairdressers. This review aims to compile and appraise evidence regarding the skin toxicity of cysteamine hydrochloride (cysteamine HCl; CAS no. 156-57-0), polyvinylpyrrolidone (PVP; CAS no. 9003-39-8), PVP copolymers (CAS no. 28211-18-9), sodium laureth sulfate (SLES; CAS no. 9004-82-4), cocamide diethanolamine (cocamide DEA; CAS no. 68603-42-9), and cocamidopropyl betaine (CAPB; CAS no. 61789-40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 104 publications
0
5
0
Order By: Relevance
“…4,5 Recent studies reported increased micronucleus frequencies in hairdressers, 19,48 a population heavily exposed to hairdressing products including oxidative hair dyes. 49 In addition, significantly higher DNA damage scores were found among hairdressers compared to controls, based on the comet assay performed on blood samples. 50 Nevertheless, linking experimental results with epidemiological studies is difficult owing to, among other things, the kinetic properties of oxidative hair dye precursors.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Recent studies reported increased micronucleus frequencies in hairdressers, 19,48 a population heavily exposed to hairdressing products including oxidative hair dyes. 49 In addition, significantly higher DNA damage scores were found among hairdressers compared to controls, based on the comet assay performed on blood samples. 50 Nevertheless, linking experimental results with epidemiological studies is difficult owing to, among other things, the kinetic properties of oxidative hair dye precursors.…”
Section: Discussionmentioning
confidence: 99%
“…The Cosmetic Ingredient Review Expert Panel has conducted a safety assessment of these persulfate salts and concluded that adverse skin and respiratory effects are known; the use of these persulfate salts, however, is classified as safe when used as oxidizing agents in hair colourants and lighteners designed for brief intermittent use completed by complete rinsing from hair and skin 18 . As safety assessment of hair cosmetic ingredients does not account for the exposure of a professional user handling the product frequently in daily working life, but rather the client or consumer, 2,19 it must be assumed that the skin contact of hairdressers might exceed the above‐described contact with persulfate salts contained in bleaching agents. This is corroborated by data from the German Information Network of Departments of Dermatology (IVDK), showing that allergic contact dermatitis caused by ammonium persulfate is a health problem, especially in hairdressers, compared with clients or self‐users 20–22 .…”
Section: Discussionmentioning
confidence: 99%
“…The Cosmetic Ingredient Review Expert Panel has conducted a safety assessment of these persulfate salts and concluded that adverse skin and respiratory effects are known; the use of these persulfate salts, however, is classified as safe when used as oxidizing agents in hair colourants and lighteners designed for brief intermittent use completed by complete rinsing from hair and skin. 18 As safety assessment of hair cosmetic ingredients does not account for the exposure of a professional user handling the product frequently in daily working life, but rather the client or consumer, 2,19 it must be F I G U R E 2 Percentage of hairdressers (n = 565) confirming availability and/or usage in the salon of dust-free bleaching powder, non-dust-free bleaching powder, bleaching cream, conventional hair colour creams with a higher concentration of hydrogen peroxide to lighten hair by 1 to 2 shades and high-lifting hair colour creams with a higher concentration of hydrogen peroxide to lighten hair by 2 to 4 shades.…”
Section: Discussionmentioning
confidence: 99%
“…Among the emulsifiers, cocamidopropyl betaine (CAPB) has been patch tested most often, enabling a reliable comparison between hairdressers and non-hairdressers. The relative risk estimated in a recent meta-analysis was 1.71 (95% CI, 1.29–2.27) [ 5 ], indicating a slightly but significantly increased risk; for some further results, see Table 1 . In view of the fact that hairdressers’ skin is much more often exposed, compared to consumer exposure on which risk assessment is based [ 1 •], preservatives and other such “everyday ingredients” seem to lead to an excess risk of contact allergy in hairdressers — if no protective gloves are worn, which is very often the case.…”
Section: Allergic Contact Dermatitismentioning
confidence: 99%